(untitled) (Itinera, 2023)
This age is characterized by the increasing humanization of a planet more and more subject to representation, visualization and prediction. The future, however, seems to herald the emergence of forces indifferent to this historical process. Our present is thus the time of this contradiction, as new forces affect all strata of our lives like a diffuse but deep trauma. My text calls for a georealism that takes into account this time, a new form of planetary realism that assumes that our time is emptied of all representable content and thus open to its own infinity, open to the encounter with what is not given, either as horizon or as memory.